A novel gene, spp91-1, suppresses the splicing defect and the pre-mRNA nuclear export in the prp9-1 mutant. - Chapon, C (1992)
Processing and export of nuclear pre-mRNA are believed to be competing processes in the nucleus. In order to identify factors which are involved in these processes, we isolated suppressors that relieve the growth defect of a prp9-1 temperature-sensitive mutant strain of Saccharomyces cerevisiae. The prp9-1 mutation was previously shown to abolish splicing and to target pre-mRNA to the cytoplasm. One of the suppressors, spp91-1, corrects the prp9-1 growth defect through partial restoration of splicing and by a complete reversion of the pre-mRNA escape phenotype. This suppressor is specific for two prp9 alleles and cannot substitute for PRP9 function. The mutant and wild-type alleles of SPP91 were cloned and sequenced. SPP91 encodes a novel protein essential for mitotic growth whose sequence contains motifs indicative of a nuclear localization. In vivo depletion of SPP91 in a prp9-1 genetic background is lethal and is associated with reduced amounts of spliced mRNA and accumulation of pre-mRNA. This observation strongly supports the hypothesis that SPP91 encodes a PRP factor. We suggest that spp91-1 increases pre-mRNA retention in the nucleus by improving the formation of the spliceosome and thereby allowing a larger proportion of the pre-mRNA molecules to be spliced.